Temporal effect of docetaxel on bone quality in a rodent model of vertebral metastases - Margarete K. Akens; Mohammedayaz Rangrez; Allison Tolgyesi; Thomas L. Willett; Cari M. Whyne (PLoS ONE, 2025)
This study investigates the effects of the anticancer drug docetaxel (DTX) and its timing of administration on tumor development and resultant bone quality in a rodent model, considering both healthy animals and those with osteolytic bone metastases secondary to intra-cardiac injection (d0) of HeLa cells. Healthy and tumor-bearing rats were treated with DTX on d7 or d14 and compared to the control (no treatment) and an additional cohort treated with Zoledronic acid (ZOL). Notably, DTX administration on d7 markedly curtailed tumor growth, as evidenced by bioluminescence and histological analysis, indicating its effectiveness in reducing bone metastases. Bone metastases were more established in animals treated with later DTX administration and ZOL, but still reduced compared to no treatment. When considering bone quality, we found that both the organic and mineral phases of bone are impacted by DTX treatment. Tumor-bearing animals exhibited decreased hydroxyproline/proline ratios reflecting change in collagen metabolism compared to healthy controls, but these decreases were only significant with no treatment or DTX administration on d14. This suggests a positive impact of early DTX treatment similar to ZOL on bone quality from an organic perspective. As well, increased CaMean and CaPeak reflecting the degree of calcification was found in healthy rats treated early with DTX, similar to that seen with ZOL compared to the tumor-bearing treated groups. Overall, early docetaxel administration reduced tumor formation and improved bone quality, suggesting its potential benefit in managing bone metastases.